ANALYSIS OF STUDENTS SCIENTIFIC CONSITENCY AND REPRESENTATION CONSISTENCY ON RECTILINEAR MOTION KINEMATICS MATERIAL GRADE X IN SMAN 8 PEKANBARU - Inike Paramita; Yennita Yennita; Fakhruddin Z (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
This study wasaimed to describe the level of student scientific consistency and representation consistency of class X SMA Negeri 8 Pekanbaru on rectilinear motion kinematisc material. The type of research was survey research. The subject of this research were 70 students. The data collection of this research used test, instrument of research used scientific consistency and representation consistency test the form of objektive matter which consist of 21 question wiht seven themes, each theme consist off three question with the same concept but presented in different representatiton. Descriptive analysis was used to analyze the data which showed the level of scientific consistency and representation consistency. The results showed that thepercentage of student at each scientific consistency level was 14.29% for consistent scientific, 20.00% for moderately consistent scientific and 65.71% for inconsistent scientific, while overall the students were at inconsistent levels for scientific consistency or that can be said they have no consistency scientific. For representation consistency, the percentage of students at each successive level was 17.14% for consistent representation, 28.57% for moderately consistent representation and 54.29% for inconsistent representation, while overall students were at moderately consistent representation level, mean that studentshave consistency representation.